Understanding the Residential Treatment Center School Academic Environment: Perspectives of Students and Teachers. Issue 2 (3rd April 2021) - Somers, Cheryl L.; Day, Angelique G.; Sepsey, Amber M.; Allegoet, Delena; Baroni, Beverly A.; Hong, Jun Sung
ABSTRACT: The purpose of the present study was to explore student and teachers' perceptions of the academic environment in an urban residential treatment center school setting, which serves female students with myriad behavioral, social, emotional, and/or academic challenges, half of which have IEPs and the remainder of which are significantly at-risk and also receive individual learning plans. Using focus group interview methods provided important information from both students ( n = 58) and teachers ( n = 27) regarding specific areas in need of improvement. The research team identified four primary themes throughout the student data and four in the teacher data. Themes that emerged throughout the student data included need for least-intrusive behavioral management, preventative strategies for behavior, differentiated instruction, and recognition. Teacher data resulted in themes of lesson plan difficulties, academic versus social-emotional well-being, balancing academic and behavioral needs, and additional assistance within the classroom. Both students and teachers voiced a number of significant concerns and provided useful ideas that can enhance the preparation and supports for teachers in training and practice, most immediately the information informed teachers in this specific context. Implications for research and broader practice are also discussed.